Ten-year experience with rituximab for induction and maintenance therapy in patients with ANCA-associated systemic vasculitis - T. V. Beketova; E. L. Nasonov (Современная ревматология, 2020)
Rituximab (RTM), a monoclonal antibody against CD20+ receptors on the membrane of B-cells, is becoming increasingly important for the induction and maintenance treatment of antineutrophil cytoplasmic antibody (ANCA)-associated systemic vasculitis (ANCA-SV). The challenge facing us is to optimize its efficacy, while limiting adverse events (AEs).Objective: to evaluate the efficacy and safety of RTM used for the induction and maintenance of remission in ANCA-SV on the basis of 10-year single-center experience.Patients and methods. The paper presents the authors’ own 10-year experience with RTM used for the induction and maintenance of remission in 103 patients with ANCA-SV, including granulomatosis with polyangiitis (GPA) (n=58), microscopic polyangiitis (MPA) (n=35), ANCA-positive eosinophilic granulomatosis with polyangiitis (EGPA) (n=4), and ANCA-negative EGPA (n=6). The duration of a follow-up after initiation of RTM treatment was more than a year (with the exception of death cases) and averaged 25 to 58 months in different ANCA-SV groups. The patients were monitored every 3 months. The intervals between repeated cycles were dependent on the time course of changes in clinical and laboratory parameters. The mean cumulative RTM dose exceeded 3 g; 75% of patients received repeated cycles of RMT usually at a cumulative dose of 0.5–1.0 g at a 4–12-month interval.Results and discussion. Repeated RTM cycles for ANCA-SV were highly effective; the clinical response rate was 97%, while 90–93% of patients with different types of ANCA-SV achieved complete clinical response. Despite the fact that the examined population included a high proportion of patients with a severe or refractory course of the disease; ANCA-SV patients showed 10% mortality rates during the entire follow-up period. Anti-B-cell therapy with RTM is of great importance in obtaining long-term optimal results, making it possible to improve ANCA-SV control and to minimize the cumulative dose of glucocorticoids. Since in ANCA-SV, the use of repeated cycles of RTM, including that at a reduced dose of 0.5 g, contributes to the higher efficiency of treatment and to the lower risk of relapse, it is advisable to perform long-term (≥2 years) RTM therapy, by controlling the parameters of clinical and immunological activities and the levels of circulating CD20+ B cells and serum immunoglobulins, deficiency of which can potentially increase the risk of infectious AEs. When planning RTM therapy, it is necessary to consider the specific features of the safety profile for individual nosological entities and to make a careful appropriate monitoring of ANCA-SV patients receiving RTM. The risk of late-onset neutropenia was highest in patients with all types of ANCA-SV (3–10%). Infections in patients with GPA and MPA constitute a substantial proportion (10–11%) in serious AEs. Management of EGPA patients requires alertness to the risk of infusion-related reactions, primarily bronchospasm.Conclusion. There is a need for further investigation of an anti-B-cell therapy strategy, including the efficacy and safety of RTM in ANCA-SV and for clarification of indications and optimal RTM treatment regimens.